2020
DOI: 10.1002/we.2559
|View full text |Cite
|
Sign up to set email alerts
|

Classical flutter analysis of composite wind turbine blades including compressibility

Abstract: For wind turbine blades with the increased slenderness ratio, flutter instability may occur at lower wind and rotational speeds. For long blades, at the flutter condition, relative velocities at blade sections away from the hub center are usually in the subsonic compressible range. In this study, for the first time for composite wind turbine blades, a frequency domain classical flutter analysis methodology has been presented including the compressibility effect only for the outboard blade sections, which are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…where M and K are the structural mass and stiffness matrices, respectively, and they are given in the previous studies of the authors. 10,27 Equation ( 17) can be solved for the eigenvalues and the corresponding eigenvectors accordingly.…”
Section: Solution Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…where M and K are the structural mass and stiffness matrices, respectively, and they are given in the previous studies of the authors. 10,27 Equation ( 17) can be solved for the eigenvalues and the corresponding eigenvectors accordingly.…”
Section: Solution Methodologymentioning
confidence: 99%
“…where the distribution of inertia terms, mass per unit length ðb 1 Þ, and mass moment of inertia about the x, y axes ðb 4 , b 5 Þ along the axis of the TWB are defined in the author's previous works. 10,27 Utilizing the strain displacement relations defined by equations ( 3) and (4) and taking the integral along the wall thickness and along the contour of the cross section of the TWB, the strain energy due to the deformation of the blade caused by the external forces can be expressed as…”
Section: Governing Differential Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that there was a reasonable similarity between flutter predictions for a full turbine versus analysis of an isolated blade uncoupled from the tower. More recently, Farsadi and Kayran (2021) developed a method to account for compressibility effects on the wind turbine blades, but the resulting flutter speeds were comparable to the classical flutter analysis methods developed by Hansen (2007).…”
Section: Introductionmentioning
confidence: 99%
“…This makes rotor blades more exposed to manufacturing errors which potentially can lead to a higher risk of laminate failure 3–5 . Thirdly, as the flexibility increases with the blade length, so does the risk of aeroelastic instabilities such as classical flutter 6–10 or vortex‐induced vibrations 11,12 . Lastly, increasing the rotor blades makes it more costly and complicated to do testing, and as the natural frequencies decrease, the time for fatigue evaluation of a rotor blade increases.…”
Section: Introductionmentioning
confidence: 99%